Long-term Structural Performance of Simplified Slab System with Steel Deck-plate and SFRC - Hong, Geonho (Proceedings of Engineering and Technology Innovation, 2017)
Slab is one of the most important members in building because it covers the largest amount of total structural members. The structural type and construction method of a slab can have a large influence on the construction period and the amount of structural materials. This study investigates a simplified slab system with simple construction procedures. The simplified slab system consists of steel deck plate and steel fiber reinforced concrete (SFRC) without conventional reinforcing bar placing in construction field. The purpose of this study is to evaluate the long-term structural performance of a simplified slab system that replaces the form work and tensile reinforcement using structural deck-plate and replaces the temperature reinforcement using steel fiber reinforced concrete. Two continuous-span slab specimens were tested and analyzed in the view-point of long-term serviceability such as deflection and crack, and evaluated the structural capacity and behavior.